Just do it! Why committed consumers react negatively to assertive ads. Issue 3 (28th January 2017) - Zemack‐Rugar, Yael; Moore, Sarah G.; Fitzsimons, Gavan J.
Abstract: Research shows that assertive ads, which direct consumers to take specific actions (e.g., Visit us; Just do it!), are ineffective due to reactance. However, such ads remain prevalent. We reexamine assertive ads, showing that their effectiveness depends on consumers' relationship with the advertising brand. Across studies, we compare committed and uncommitted consumers' reactions to assertive ads. We find that because committed (vs. uncommitted) brand relationships involve stronger compliance norms, assertive ads create greater pressure to comply for committed consumers. Specifically, we propose and show that committed consumers anticipate feeling guilty if they ignore an assertive message, creating pressure to comply. Pressure to comply increases reactance, which paradoxically reduces compliance, ultimately leading to decreased ad and brand liking as well as decreased monetary allocations to the brand. Our results show the perils that assertive ads pose for marketers and their most valuable customers.